2011
DOI: 10.1258/ebm.2011.011066
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of induced bone marrow mesenchymal stem cells improves the cardiac function of rabbits with dilated cardiomyopathy via upregulation of vascular endothelial growth factor and its receptors

Abstract: Bone marrow mesenchymal stem cells (BMMSCs) have shown promise in repairing injured myocardium. However, few studies have explored the potential of BMMSC transplantation for dilated cardiomyopathy (DCM). In this study we aimed to examine whether BMMSC transplantation improves the cardiac function of dilated cardiomyopathy and investigate the underlying mechanism. We established a DCM model in rabbit, then transplanted BMMSCs induced by 5-azacytidine into the rabbit, and determined the left ventricular pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Accumulating data in the literature has demonstrated that transplanted BMSCs may improve cardiac function in the rat model of acute or chronic myocardial infarction (MI) [810]. Therefore, cell therapy with BMSCs has been attempted to attenuate LV remodeling and preserve cardiac function in the rat model of DCM [11,12]. More significantly, a randomized double-blind and placebo-controlled trial also demonstrated the safety and efficacy of autologous BMSCs transplantation in human patients with DCM [13].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data in the literature has demonstrated that transplanted BMSCs may improve cardiac function in the rat model of acute or chronic myocardial infarction (MI) [810]. Therefore, cell therapy with BMSCs has been attempted to attenuate LV remodeling and preserve cardiac function in the rat model of DCM [11,12]. More significantly, a randomized double-blind and placebo-controlled trial also demonstrated the safety and efficacy of autologous BMSCs transplantation in human patients with DCM [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental evidence suggests that the blood flow is the key of all the elements [1]. Abnormality of vascular net can contribute to retardation of development in embryo [2], cardiomyopathies in heart [3,4], progression and metastasis in malignancy [5], and so on.…”
mentioning
confidence: 99%
“…As a result of the ultimately poor prognosis even with standard medical management of DCM, interest has developed in regenerative treatments such as stem-cell therapy (Mu et al 2011). Cardiac cellular transplantation seeks to maintain or even improve left ventricular function with implantation of progenitor cells capable of decreasing fibrosis, increasing neovascularization, and less likely, producing new cardiomyocytes .…”
Section: Discussionmentioning
confidence: 99%
“…, Mu et al . ). Therefore, similar improvements may be found with naturally occurring DCM in Dobermanns, even in the occult stage of the disease.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation